Comportamento defensivo de abelhas africanizadas em relação à perseguição e ao número de ferroadas em Mossoró-RN - Silva, Armando Ferreira da (Universidade Federal Rural do Semi-Árido, 2008)
Africanized bees have an aggressive behavior that always receives the influence of weather conditions, mainly by air humidity, temperature and heredity. This study aimed to evaluate the level of aggressiveness of Africanized bees, through the following observations: the time for the bees are settled, the number of sting left and away from persecution. We used 50 colonies of Apis mellifera (Africanized bees) and the tests performed within days in day 04, 05 and 06/04/08 at 10am in the morning with the sun between clouds and vegetation florida. The bait for bees was a square of chamois, 2 cm x 2 cm, with a cordon of white, 20 cm in length which was cantilevered to a distance of 5 cm in front of Alvada for 60 seconds, then followed that walking to have the distance of persecution. It was found that the time needed to happen that the irate bees was 2.45 seconds after the start of these comments and calm down an average of 22.5 minutes. One minute after the start of the attack, we obtained a 61.5 average number of sting, with a prosecution in an average distance of 652, 47 meters. The results show that these Africanized bees have an above average defensive studied so far, here in Brazil
Keywords: Apicultura; Abelha; Ferroadas; Beekeeping; Bees; sting; CIENCIAS AGRARIAS::MEDICINA VETERINARIA